Hotel and business in modern France and Germany - E. B. Botavina; Т. A. Kaydalova (Вестник университета)
This article discusses the historical prerequisites for the emergence of tourism in Europe and analyzes its historically determined features. The authors show the characteristic national aspects of the tourism industry in France and Germany. The historical and cultural background and prospects of European tourism are also studied against the backdrop of political, economic and cultural processes in modern Europe. The article also shows the main elements of the tourism business in the countries under consideration, including their hotel component. Travel promotes cultural exchange and education, enhances the quality of life, strengthens health and supports the cohesion of people. The COVID-19 pandemic has dramatically changed people’s desire to travel. Before the pandemic, the German tourism industry planned to raise the profile of this sector of the economy, since 4 % of the value added in Germany is directly related to tourism. The economics of the tourism industry also has an impact on other sectors of the economy such as the mobility sector. Tourism is a key driver of regional development in many regions of the world, including Germany and France. The overall goal may be to use this influence wisely and create additional value for tourists and for the local population.